Pengabdian Masyarakat dalam Rangka Pengaplikasian Penelitian: Kasiat Tanaman Obat Bidang Mikrobiologi - Widodo Widodo; Sunarto Sunarto; Fauzan Ma'ruf; Nanik Aryani Putri; Sy. Didik Widiyanto (Jurnal LINK, 2026)
Morinda citrifolia is efficacious for treating several degenerative diseases such as cancer, tumors, and diabetes. These substances have been proven to be antibacterial substances due to infectious bacteria such as, Proteus morganii, Bassilus subtilis, Staphylococus aureus, Pseudomonas aeruginosa and Echercia coli. This community service aims to utilize noni fruit, ginger, and honey as a form of application for the application of research results in community outreach held in Bangetayu Wetan village. Noni fruit that has been fermented is then tested against Eschericia coli and Salmonella typhi bacteria using micro titers. The results showed that at a concentration of 25%, there was inhibition of the growth of Salmonella typhi bacteria, while for Escheria coli at a concentration of 25%, growth inhibition began to occur. With a very large concentration of the taste of this fermentation, the acidity and smell of noni that is typical for some people may find it difficult to accept. Based on the results of the community service to the community, the community welcomes the results of the community that have been distributed to the entire community properly.